Magnetic Resonance Imaging Findings in Childhood Epilepsy at a Tertiary Hospital in Kenya - Samia, Pauline (Front Neurol, 2021)
Background: Neuroimaging is important for determining etiology and guiding care in early childhood epilepsy. However, access to appropriate imaging in sub-Saharan Africa is modest, and as a consequence, etiological descriptions of childhood epilepsy in the region have been limited. We sought to describe MRI findings in children with epilepsy presenting to a tertiary hospital in Nairobi, Kenya, over a 6-year period of routine care. Materials and Methods: We undertook a retrospective review of MRI findings of children aged between 0 and 18 years with a diagnosis of epilepsy presenting to the pediatric neurology department of Aga Khan University Hospital in Nairobi, Kenya, between January 2014 and July 2020. Over this period, the hospital had 1.5T MRI machines (GE1.5T Signa Excite and GE 1.5T Signa Explorer) and a 3T MRI machine (Philips 3T Ingenia). MRI images were independently reviewed by two study radiologists, and the findings were summarized and categorized into a study database. Related clinical and electroencephalographic (EEG) details were extracted from patient records. Categorical data analysis methods were applied to investigate for relationships between clinically relevant neuroimaging findings and key clinical and EEG observations. Results: Over the study period, 288 children with a confirmed diagnosis of epilepsy had an MRI. They were of median age of 6 [interquartile range (IQR) 2–11] years. Ninety-five (33%) children had abnormal findings on imaging. The most common findings were encephalomalacia related to chronic infarcts (n = 18: 6.3%), cerebral atrophy (n = 11: 3.8%), disorders of neuronal migration (n = 11: 3.8%), periventricular leukomalacia (n = 9: 3.1%), and hippocampal sclerosis (n = 8: 2.8%). Findings related to infectious etiology were only observed in four children. Clinical comorbidity and inter-ictal epileptiform activity on EEG were independently associated with abnormal findings on imaging. Conclusion: Up to a third of the children who underwent an MRI had a positive yield for abnormal findings. Imaging findings related to infectious etiologies were little observed in our cohort, in contradistinction to etiology studies in similar settings. At the time of the study, comorbidity and inter-ictal epileptiform activity on EEG were associated with abnormal findings on imaging and should be considered in informing prioritization for imaging in childhood epilepsy in this setting.